PROBLEMATIKA PEMBELAJARAN FIKIH DI PONDOK PESANTREN AL FATAH DESA TEMBORO KECAMATAN KARAS KABUPATEN MAGETAN - Muhammad Luthvi Al Hasyimi (LP3M Sekolah Tinggi Agama Islam Ma'arif Magetan, 2021)
‘Pondok Pesantren’ (Islamic boarding schools) are educational institutions with various and different education system. One of them is printing fuqoha' or fiqh experts. The Al Fatah Temboro Islamic boarding school is quite concerned about studying fiqh. This is shown in the Al fatah Temboro Islamic boarding school curriculum, fiqh material has been studied from the first grade to the last grade with nine grade levels and taken for ten years. Even so, there are still problems in learning jurisprudence at the Al Fatah Temboro Islamic Boarding School. Among them is the imbalance between the amount of material that must be studied and the lack of time, the diverse backgrounds and languages ??of the students and the lack of practical methods in learning fiqh.